2014
DOI: 10.1177/0363546514555506
|View full text |Cite
|
Sign up to set email alerts
|

Arm Pain in Youth Baseball Players

Abstract: A majority of healthy (actively competing) youth baseball players report at least some baseline arm pain and fatigue, and many players suffer adverse psychosocial effects from this pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 8 publications
1
82
0
Order By: Relevance
“…In accordance with the increase in the number of participants in overhead throwing sports, there has been an increase in the incidence of upper extremity injuries in the past decades 53. To date, 25% of Major League pitchers and 15% of Minor League pitchers have had Tommy John surgery at some point in their career 5.…”
Section: Considerationmentioning
confidence: 99%
“…In accordance with the increase in the number of participants in overhead throwing sports, there has been an increase in the incidence of upper extremity injuries in the past decades 53. To date, 25% of Major League pitchers and 15% of Minor League pitchers have had Tommy John surgery at some point in their career 5.…”
Section: Considerationmentioning
confidence: 99%
“…Lyman et al 2) found that at least 50% of youth pitchers had experienced pain in the shoulder and elbow while throwing. In an epidemiological study of 218 baseball players aged 8 to 18 years, Makhni et al 3) reported that only 26% of players never experienced arm pain related to throwing. Additionally, it has been reported that 5% of youth baseball pitchers sustain shoulder or elbow injuries severe enough to either require surgery or result in their retirement from the sport 4) .…”
Section: Introductionmentioning
confidence: 99%
“…9,10,15 In a survey of youth baseball players, only 26% reported that their arm never hurt while throwing. 11 Pitching, in particular, is a common mechanism of injury in baseball. 3,12 Olsen et al 12 found that pitchers with injuries to the shoulder and elbow pitched significantly more months per year, games per year, innings per game, pitches per game, pitches per year, and warm-up pitches per game.…”
mentioning
confidence: 99%